Isolation and characterization of plant growth-promoting rhizobacteria from wheat rhizosphere and their effect on plant growth promotion - Majeed, Afshan; Abbasi, M. Kaleem; Hameed, Sohail; Imran, Asma; Rahim, Nasir (Frontiers in Microbiology, 2015)
Abstract The present study was conducted to characterize the native plant growth promoting bacteria from wheat rhizosphere and root-endosphere in the Himalayan region of Rawalakot, Azad Jammu and Kashmir (AJK), Pakistan. Nine bacterial isolates were purified, screened in vitro for plant growth promoting (PGP) characteristics and evaluated for their beneficial effects on the early growth of wheat (Triticum aestivum L.). Among nine bacterial isolates, seven were able to produce indole-3- acetic acid in tryptophan-supplemented medium; seven were nitrogen fixer, and four were able to solubilize inorganic phosphate in vitro. Four different morphotypes were genotypically identified based on IGS-RFLP fingerprinting and representative of each morphotype was identified by 16S rRNA gene sequencing analysis except Gram positive putative Bacillus sp. Based on 16S rRNA gene sequence analysis, bacterial isolates AJK–3 and AJK-9 showing multiple PGP-traits were identified as Stenotrophomonas spp. while AJK-7 showed equal homologies to Acetobacter pasteurianus and Stenotrophomonas specie. Plant inoculation studies indicated that these PGPR strains provided a significant increase in shoot and root length, and shoot and root biomass. A significant increase in shoot N contents (up to 76%) and root N contents (up to 32%) was observed over the un-inoculated control. The study indicates the potential of these PGPR for inoculums production or biofertilizers for enhancing growth and nutrient content of wheat and other crops under field conditions. The study is the first report of wheat associated bacterial diversity in the Himalayan region of Rawalakot, AJK.